Synthesis method and application of recyclable carbonyl sulfide removal carbon-based fine desulfurizing agent
By designing a monodispersed metal modified carbon catalyst, the problems of high energy consumption and poor catalyst stability in the COS removal process in the prior art were solved, efficient COS hydrolysis and conversion into elemental sulfur were achieved, and the application performance of the catalyst was significantly improved.
Patent Information
- Application Number
- CN202411664702.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has problems such as high energy consumption, waste liquid generation, equipment loss and catalyst stability reduction when removing carbonylsulfide (COS) in blast furnace gas. Especially when oxygen is present, the deactivation rate of metal oxide-based catalysts is high and it is difficult to regenerate and utilize.
A monodispersed metal modified carbon catalyst is designed to produce a solid by stirring the carbon-nitrogen precursor and the transition metal precursor in a solvent, which is then calcined and pickled and dried under an inert atmosphere, and finally reduced under a reducing atmosphere to form a catalyst with a high specific surface area and high metal content. The catalyst still maintains high catalytic activity in the presence of oxygen and can be regenerated and reused by Ar high temperature treatment.
This catalyst exhibits excellent activity in COS hydrolysis reaction, can effectively convert COS into elemental sulfur, maintain stability in the presence of oxygen, and can be recycled and recycled, without affecting performance, which is better than the traditional Al2O3 catalyst.
Smart Images

Figure BDA0005144307980000051 
Figure BDA0005144307980000061 
Figure HDA0005144307990000011
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a recyclable carbon-based fine desulfurizing agent and its application in one-step conversion of carbonyl sulfide into elemental sulfur, belonging to the field of environmental protection. Background Art
[0002] Carbonyl sulfide (COS), as a highly toxic and colorless organic sulfide, is widely present in the tail gas of blast furnace gas and coke oven gas produced by steel smelting. The presence of COS will not only deactivate the catalyst and corrode the reaction equipment, but also seriously affect the high-value utilization of blast furnace gas. Therefore, efficient removal of COS from blast furnace gas is an important guarantee for achieving high-value utilization of blast furnace gas. At present, the main methods for removing COS can be divided into two categories: wet desulfurization and dry desulfurization. Wet desulfurization is to wash industrial tail gas with liquid absorbent (mostly organic amine solvent). However, wet desulfurization will produce a large amount of waste liquid and consume too much energy, making its industrial operation cost high; and alkaline liquid will also bring inevitable equipment loss. Dry desulfurization includes adsorption, catalytic oxidation, hydrogenation conversion, and catalytic hydrolysis. Among these methods, the adsorption method often requires a large amount of desulfurizer due to the limited amount of gas treated by the unit mass of adsorbent, and has the defects of large equipment, large floor space, and high operating technology requirements. Although the processing capacity of the hydrogenation conversion method is enhanced compared with adsorption, it requires the consumption of additional hydrogen sources. The oxidation method requires COS to burn with O2 to generate S element, which is prone to fire, explosion and other hazards. The hydrolysis method has the characteristics of simple process, low energy consumption, mild reaction conditions, and no need for additional hydrogen sources. It has been widely used in industrial processes to remove COS.
[0003] At present, the commonly used COS hydrolysis catalysts in industry are metal oxide catalysts represented by Al2O3 and metal oxide-based catalysts modified with alkali metals such as K and Na. Although metal oxide catalysts have good catalytic activity and stability for the hydrolysis of pure COS, the raw gas also contains impurities such as water vapor, oxygen, hydrogen and carbon dioxide gas under working conditions. In particular, when oxygen is present, the stability of the metal oxide-based catalyst is greatly reduced. In addition, since the metal sites of the metal oxide-based catalyst are destroyed, it is often difficult to reactivate and utilize them after deactivation, which greatly limits the application of this type of catalyst.
[0004] Monodisperse metal-modified carbon materials have been widely used in many fields due to their 100% metal atom utilization and unique electronic properties. They not only have the structural characteristics of carbon-based materials such as large specific surface area and high pore volume, but also have ultra-high catalytic performance of metal sites, and compared with metal catalysts, their metal usage is greatly reduced. Therefore, monodisperse metal-modified carbon catalysts are expected to become the next generation of high-performance industrial catalysts to replace traditional metal-based and carbon-based industrial catalysts. In the COS hydrolysis reaction, the active sites of traditional carbon-based catalysts are relatively inert, and the efficiency of catalytic conversion of COS is low; metal-based catalysts are highly active, but are prone to form metal sulfates and metal sulfides, especially in the presence of impurity gases such as oxygen, the deactivation rate is too fast and cannot be regenerated. Monodisperse metal-modified carbon catalysts have the advantages of both carbon-based catalysts and metal-based catalysts, and their porous structure can effectively reduce the damage of impurity gases and dust in blast furnace gas to the active sites of the catalyst. It is an efficient COS hydrolysis industrial catalyst with great application prospects in the future. Summary of the invention
[0005] In view of the existing technical problems, the purpose of the present invention is to design a recyclable carbonyl sulfide one-step conversion into elemental sulfur carbon-based fine desulfurization agent. The monodisperse metal-modified carbon catalyst prepared by the present invention has a high specific surface area, pore volume and metal content, and has a high COS hydrolysis performance. At the same time, in the presence of impurity gases such as oxygen, it still has a high catalytic activity and can be recycled and regenerated by Ar high temperature treatment.
[0006] The present invention provides a synthetic method for converting carbonyl sulfide into a single sulfur carbon-based fine desulfurizing agent which can be recycled and regenerated in one step, comprising the following steps:
[0007] (1) Dissolve a carbon nitrogen precursor and a transition metal precursor in a solvent and stir to react at room temperature.
[0008] (2) The turbid liquid obtained in step (1) is centrifuged and dried to obtain solid a.
[0009] (3) calcining the solid a obtained in step (2) under an inert atmosphere to obtain a solid b.
[0010] (4) The solid b obtained in step (3) is acid-washed, dried, and then reduced in a reducing atmosphere to obtain a monodisperse metal-modified carbon-based catalyst.
[0011] Furthermore, in step (1), the solvent is one or more of methanol, ethanol or water, the carbon nitrogen precursor is one or more of 2-methylimidazole, 4-methylimidazole, N-methylimidazole, and the transition metal precursor is one or more of zinc nitrate, nickel nitrate, cobalt nitrate, copper nitrate or iron nitrate.
[0012] Furthermore, the stirring reaction time in step (1) is 5 to 20 hours.
[0013] Furthermore, in step (2), the drying temperature is 50 to 130° C., and the drying time is 3 to 15 hours.
[0014] Furthermore, the inert atmosphere in step (2) is one or a combination of two or more of argon, helium, and nitrogen, and the heating rate of the heating program is 1 to 10° C. / min.
[0015] Furthermore, the calcination temperature in step (2) is 600-1200° C., and the calcination time is 1-5 hours.
[0016] Furthermore, the acid solution in step (3) is one or more of hydrochloric acid, sulfuric acid, and nitric acid; the reducing atmosphere is a combination of one or more of H2, CO or CH4, the reduction temperature is 200-700°C, and the reduction time is 1-5h.
[0017] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0018] (1) The present invention prepares a monodisperse metal-modified carbon catalyst with high specific surface area, pore volume and metal atom content, which can fully expose the active sites and promote the adsorption and activation of reactants during the reaction, which is beneficial to the hydrolysis reaction.
[0019] (2) After the catalyst is treated with a reducing atmosphere, the coordination microenvironment around the metal atoms is improved, and a stable metal-nitrogen structure is formed as a catalytic active site. The unreduced catalyst does not have such an active site, which can effectively prevent the metal from reacting with sulfur to form metal sulfates and metal sulfides, which would poison the catalyst.
[0020] (3) The catalyst provided by the present invention has excellent COS hydrolysis performance, which is superior to the traditional Al2O3 catalyst; and O2 is no longer regarded as an impurity gas, but as a reaction gas, COS hydrolysis and H2S oxidation reactions are carried out simultaneously on a monodisperse metal-modified carbon catalyst, and COS is converted into S elemental substance in one step. The Al2O3 catalyst currently used in industry cannot achieve this effect.
[0021] (4) The catalyst provided by the present invention can be recycled and regenerated after being purged with high-temperature Ar gas without affecting its performance. Under the same conditions, the Al2O3 catalyst cannot be regenerated and used. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0023] Figure 1This is a scanning electron microscope image of the COS hydrolysis catalyst prepared in Example 3.
[0024] Figure 2 The figure is a comparison chart of the COS hydrolysis activities of the COS hydrolysis catalysts prepared in Examples 1, 2, 3 and Comparative Examples 2, 3.
[0025] Figure 3 The COS hydrolysis activity diagram of the catalyst prepared in Example 3 and Comparative Example 1 in the presence of O2 and the catalyst performance change diagram after Ar high-temperature reduction. DETAILED DESCRIPTION
[0026] The specific implementation method of the present invention is described in detail below. The specific implementation method described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0027] Example 1
[0028] 13 g of 2-methylimidazole was dissolved in 160 ml of methanol and recorded as A. 12 g of zinc nitrate was dissolved in 130 ml of methanol and recorded as B. B was added to A under stirring and stirred at room temperature overnight. Then, a white solid was obtained by centrifugal drying, and the temperature was increased to 900° C. at a heating rate of 2° C. / min under an argon atmosphere and maintained for 2 h to obtain a black solid. The black solid was then stirred in a 1 M HCl solution for 8 h, and finally washed to neutrality and dried to obtain Example 1.
[0029] The specific surface area and metal content of Example 1 are shown in Table 3. The specific surface area is 680 m 2 / g, and the content of metal Zn is 8.9wt.%.
[0030] Example 2
[0031] Dissolve 13g of 2-methylimidazole in 160ml of methanol and record it as A. Dissolve 12g of zinc nitrate in 130ml of methanol and record it as B. Add the solution in B to A under stirring and stir at room temperature overnight. Then centrifuge and dry to obtain a white solid, heat it to 900℃ at a heating rate of 2℃ / min under argon atmosphere and keep it for 2h to obtain a black solid, then stir the black solid in 1M HCl solution for 8h, and finally wash it to neutrality and dry it. Take the obtained catalyst, heat it to 400℃ at a heating rate of 2℃ / min under pure H2 conditions and keep it for 2h to obtain Example 2.
[0032] Example 3
[0033] Dissolve 13g of 2-methylimidazole in 160ml of methanol and record it as A. Dissolve 12g of zinc nitrate in 130ml of methanol and record it as B. Add the solution in B to A under stirring and stir at room temperature overnight. Then centrifuge and dry to obtain a white solid, heat it to 900℃ at a heating rate of 2℃ / min under argon atmosphere and keep it for 2h to obtain a black solid, then stir the black solid in 1M HCl solution for 8h, and finally wash it to neutrality and dry it. Take the obtained catalyst, heat it to 600℃ at a heating rate of 2℃ / min under pure H2 conditions and keep it for 2h to obtain Example 3.
[0034] The scanning electron microscope image of Example 3 is as follows Figure 1 As shown, the catalyst surface morphology is carbon particles of about 200 nm.
[0035] The specific surface area and metal content of Example 3 are shown in Table 3. The specific surface area is 1187 m 2 / g, and the content of metal Zn is 11.7wt.%, both higher than that in Example 1.
[0036] Comparative Example 1
[0037] Commercial Al2O3 catalyst.
[0038] Comparative Example 2
[0039] 2 g of KOH was dissolved in 60 mL of deionized water, and then 4 g of ethylenediaminetetraacetic acid and 3.5 g of melamine were added, and the mixture was stirred evenly for 0.5 h, and then dried in an oven at 80 ° C to obtain a white solid, and then heated to 800 ° C at a heating rate of 5 ° C / min under an argon atmosphere and maintained for 2 h to obtain a black solid, and then the black solid was stirred in a 1M HCl solution for 8 h, and finally washed to neutral and dried to obtain Comparative Example 2.
[0040] Comparative Example 3
[0041] Dissolve 1g of anhydrous glucose, 3g of dicyandiamide and 10g of sodium chloride in 40mL of deionized water, then stir the solution in a 70°C oil bath for 1h, and place the solution in a freeze drying oven for 48h. Place the dried white powder in a tube furnace, heat it to 800°C at a heating rate of 2°C / min under an inert atmosphere and keep it for 2h to obtain a black powder. Wash the obtained black powder with deionized water for 8h, then centrifuge and filter to remove NaCl in the sample, and then transfer it to a 60°C oven for drying for 24h to obtain Comparative Example 3.
[0042] Comparative Example 4
[0043] 13 g of 2-methylimidazole was dissolved in 160 ml of methanol and recorded as A. 12 g of zinc nitrate was dissolved in 130 ml of methanol and recorded as B. B was added to A under stirring and stirred at room temperature overnight. Then, a white solid was obtained by centrifugal drying, and the temperature was increased to 900° C. at a heating rate of 2° C. / min under an argon atmosphere and maintained for 2 h to obtain a black solid, thereby obtaining Comparative Example 4.
[0044] Example 4
[0045] This example is used to illustrate the COS hydrolysis reaction method provided by the present invention.
[0046] The catalysts prepared in Examples 1, 2, 3 and Comparative Examples 2 and 3 were used to test the COS hydrolysis activity, wherein the catalyst loading was 150 mg, the COS concentration was 100 ppm, the total reaction gas flow was 50 ml / min, the reaction temperature was 100° C., the water vapor content was 30 vol%, and the COS hydrolysis activity test conditions and results are shown in Table 1 and Attached Figure 2 It is knowable.
[0047] Table 1. COS hydrolysis test results of Examples 1, 2, 3 and Comparative Examples 2 and 3
[0048]
[0049] From Table 1 and Appendix Figure 2 It can be seen that the catalyst prepared by Example 3 maintained a 100% conversion rate for carbonyl sulfide for 22 hours, and the catalyst prepared by Example 3 had the best COS hydrolysis activity compared with other examples and comparative examples. This is because after hydrogen treatment at high temperature, the specific surface area, pore volume, metal content, etc. of the sample increased, the number of exposed active sites increased, and the coordination microenvironment of the single metal site was changed, thereby improving the catalytic performance.
[0050] Example 5
[0051] The COS hydrolysis catalyst prepared in Example 3 and Comparative Example 1 was used to carry out a one-step conversion of COS into elemental S and a temperature-raising activation continuous test, wherein the catalyst loading was 100 mg, the COS concentration was 100 ppm, the total reaction gas flow was 50 ml / min, the reaction temperature was 100° C., the water vapor content was 30 vol%, the O2 content was 10000 ppm, and the COS hydrolysis activity results were shown in Table 2 and the attached Figure 3As shown. The catalyst prepared by Example 3 can maintain a high conversion rate for COS in the presence of O2 and can convert COS into elemental S in one step, and the deactivated catalyst still has a high conversion rate for COS after Ar heating activation, which fully demonstrates the excellent COS hydrolysis activity and regeneration ability of the catalyst prepared by this method. However, the COS conversion rate of the commercial Al2O3 catalyst drops rapidly in the presence of O2, and its catalytic performance cannot be restored after Ar heating activation, indicating that the performance of the catalyst prepared by the present invention is far superior to that of commercial alumina and has a higher resistance to impurity gases.
[0052] Table 2. Circulation regeneration COS hydrolysis test results of Example 3 and Comparative Example 1
[0053]
[0054] Table 3. Specific surface area and metal content of Example 1 and Example 3
[0055] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Metal content (wt.%) Example 1 680 0.22 8.9 Example 3 1087 0.37 11.7
[0056] The above is only a preferred experimental scheme of the present invention, and is not intended to limit the present experimental invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based fine desulfurizing agent that can recycle and regenerate carbonyl sulfide into elemental sulfur in one step, characterized in that: The following steps are involved: (1) dissolving a carbon nitrogen precursor and a transition metal precursor in a solvent and stirring the mixture at room temperature for reaction; (2) centrifuging and drying the turbid liquid obtained in step (1) to obtain solid a; (3) calcining the solid a obtained in step (2) under an inert atmosphere to obtain a solid b; (4) The solid b obtained in step (3) is acid-washed, dried, and then reduced under a reducing atmosphere to obtain the target product, a carbon-based fine desulfurization agent.
2. The preparation method according to claim 1, characterized in that In step (1), the solvent is one or more of methanol, ethanol or water, the carbon nitrogen precursor is one or more of 2-methylimidazole, 4-methylimidazole, N-methylimidazole, the transition metal precursor is one or more of zinc nitrate, nickel nitrate, cobalt nitrate, copper nitrate or iron nitrate, and the stirring reaction time is 5 to 20 hours.
3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 50-130° C., and the drying time is 3-15 hours.
4. The preparation method according to claim 1, characterized in that: The heating rate of the tubular furnace in step (3) is 1 to 10°C / min.
5. The preparation method according to claim 1, characterized in that: The inert atmosphere in step (3) is one or a combination of two or more of argon, helium, and nitrogen. The calcination temperature is 600 to 1200° C. and the calcination time is 1 to 5 hours.
6. The preparation method according to claim 1, characterized in that: In step (4), the acid solution is one or more of hydrochloric acid, sulfuric acid, and nitric acid; the reducing atmosphere is a combination of one or more of H2, CO, or CH4; the reduction temperature is 200 to 700°C; and the reduction time is 1 to 5 hours.
7. Use of a carbon-based fine desulfurizing agent synthesized by the preparation method according to any one of claims 1 to 6 as a catalyst in a one-step conversion reaction of carbonyl sulfide into elemental sulfur.
8. The use according to claim 7, characterized in that: The catalyst is applied to the carbonyl sulfide hydrolysis reaction containing water vapor and oxygen to convert the carbonyl sulfide into elemental sulfur in one step.
Citation Information
Patent Citations
Carbonyl sulfide hydrolysis catalyst with poisoning resistance and preparation method thereof
CN115301245A
Heterogeneous cobalt-based catalyst as well as preparation method and application thereof
CN116422360A
Integrated renewable catalyst for converting carbonyl sulfide into sulfur as well as synthesis method and application of catalyst
CN117443382A
Preparation method of catalyst for converting organic sulfur into elemental sulfur through one-step method and desulfurization method of catalyst
CN118649695A
Cited By
A supported carbon-based adsorbent for removing COS from blast furnace gas at low temperature and a preparation method thereof
CN120169333B